Descontaminação de sólidos de perfuração via aquecimento por microondas - Santos, Jéssika Marina dos (2014)
Contaminated cuttings with drilling fluid are the waste of drilling operations. A more restrictive environmental legislation and the need to reduce drilling costs has led to the optimization of solid-liquid separation and recycling of drilling fluids. Microwave drying has been identified as an alternative to promote this solid-liquid separation. By this process, the components of the material are heated individually and instantaneously, resulting in a selective heating. This study aims to investigate the effect of various process variables such as heating time, temperature control, bed height, particle size, fluid composition and addition of carrier gas in the removal of non-aqueous phase of cuttings contaminated with drilling fluid. Residual contents of n-paraffin and moisture, and removal percentage of fluid and organic phase were the analyzed responses. The tests showed that the cuttings subjected to microwave drying reach levels of residual n-paraffin lower than those achieved by the current technology used. Moreover, those variables, such as bed height and particle size of cuttings, significantly affect the process by influencing the penetration depth of the electromagnetic energy and the material heating rates. It was also observed that the higher the moisture content of the material subjected to drying by microwaves, the higher will be the removal of the organic phase.